Value at Risk Evaluation of Defined Contribution and Defined Benefit Pension Plans - Fadilah, Alya; Anggraeni, Andini Setyo; Reza, Widya (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
Pension funds such as the Defined Benefit Pension Program (DBPP) and the Defined Contribution Pension Program (DCPP) have risks that need to be managed carefully. Previous research has looked at VaR in other contexts, but no one has specifically discussed VaR in pension funds, especially DBPP and DCPP. The main objective of this research is to determine the VaR value for the two pension programs and analyze the risk differences between DBPP and DCPP. The method used is VaR measurement with Monte Carlo simulation based on data from January 2015 to July 2023. The research results obtained from these measurements show that DBPP provides the largest potential maximum loss (VaR) value for the next 1 month period compared to DCPP.